A Flexible and Ultra‐Wideband Terahertz Wave Absorber Based on Pyramid‐Shaped Carbon Nanotube Array via Femtosecond‐Laser Microprocessing and Two‐Step Transfer Technique. Issue 11 (6th February 2022) - Xiao, Dongyang; Chen, Weiliang; Sun, Leimeng; Zhu, Minmin; Ng, Zhi Kai; Teo, Edwin Hang Tong; Zhang, Jingyu; Hu, Fangjing
Abstract: High and uniform absorption capabilities of terahertz (THz) waves in an ultra‐broadband range is desirable for many THz functional devices. Nowadays, it is still challenging to fabricate flexible THz absorbers with a uniformly high absorptance across the entire THz band merely based on traditional bulk materials. Engineered metamaterials absorbers utilize impedance matching to reduce the surface reflection at a single frequency, and can achieve near‐unity power absorption within a relatively narrow bandwidth. In this work, a fabrication strategy combining a femtosecond‐laser microprocessing process and a two‐step‐transfer technique is demonstrated for the realization of vertically‐aligned carbon nanotube (VACNT) arrays with pyramid‐shaped unit cells for THz wave absorptions. To transfer the structured VACNT array from the silicon to the flexible PDMS/Cu/PET substrate, the temperature and pressure dependences of the transfer process are systematically investigated. The fabricated THz absorber demonstrates an average power absorptance over 98.9% from 0.1 to 2.5 THz, and can function well in bended states and after 300 times bending cycles. The proposed fabrication strategy is expected to be used for the patterning of VACNTs and other nanomaterials, and advance the development of novel THz devices for various applications. Abstract : A fabrication strategy combining a femtosecond‐laser microprocessing process and a two‐step‐transfer technique is proposed to realize antireflection structures of vertically‐aligned carbon nanotube (VACNT) arrays for terahertz (THz) wave absorbing applications. The dependence of temperature and pressure on the transfer process are systematically investigated, and experimental results show an average power absorptance of 98.9% from 0.1 to 2.5 THz for the flexible THz absorber.